User-specific touch interfaces: a viable solution for an aging society?. Issue 9 (4th July 2022) - Shahal, Avner; Spang, Robert P.; Minge, Michael; Trahms, Carola; Voigt-Antons, Jan-Niklas
ABSTRACT: Touch interaction has established a dominating role in the realisation of Human–Machine Interfaces. However, to be able to use touch effectively and efficiently, users have to comply with particular prerequisites. Due to age-related changes, such as the decline of tactile accuracy and speed, especially elderly users often struggle with the touch modality. Interfaces that adapt to specific user characteristics could be a promising solution to overcome this problem. Notwithstanding the advantages of adaptive systems, perceived changes in the user interface can reduce the system's predictability and transparency. The present study compares three approaches concerning the adaptation of touch button sizes: no adaptation and adaptation with visible and invisible feedback. Results show that especially elderly users substantially benefit from an adaptive approach. Furthermore, data shows that the type of adaptation supports different usage goals. While adaption with visual feedback enables a higher interaction speed, invisible adaptation leads to a higher degree of accuracy.